Pengaruh model discovery learning terhadap peningkatan motivasi belajar IPA Siswa - Yosef Patandung (Universitas Negeri Makassar, 2017)
The purpose of this study were to describe the implementation of discovery learning model in science learning, learning motivation, and to examine the influence of the application of discovery learning model toward the motivation of the fifth grade students of SDN Mannuruki in science subjects. Research is a quantitative research which used true experimental design with pre-test-post-test control group design. The result of this research shows that: (i) The implementation of discovery learning model at the experimental group followed the syntax of discovery learning model namely observation, constructing questioning, making hypothesis, collecting data and making conclusion; (ii) The motivation of the fifth grade students of SDN Mannuruki in science learning categorized as medium before applying the discovery learning model; (iii) There is a significant effect of the implementation of discovery learning model toward the motivation of the fifth grade students of SDN Mannuruki in Science learning where the significant value is 0.0015 < α 0.05.. Therefore, it can be concluded that there is a significant effect of the implementation of discovery learning model toward the motivation of the fifth grade students of SDN Mannuruki in science learning